(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The article focuses on the ethical question of the macro-allocation of healthcare resources and the problems of public health, strictly related to the micro-allocation problem and the patients’ access to care. The author criticizes the utilitarian criteria and argue in favour of the clinical criteria, in the framework of the ethical values of responsibility and solidarity.